Avaliação da microinfiltração marginal em restaurações de classe V em resina composta em dentes bovinos: efeito de diferentes equipamentos para preparos cavitários e sistemas adesivos - Teixeira, Symone Cristina [UNESP] (2000)
The aim of this study was to evaluate in vitro the marginal microleakage of class V prepared with high-speed (HS}, air abrasion (AA), ultrasound (US) and Er:YAG /aser(LA), and restored with multi-step or self-etching adhesives systems. One-hundred-sixty incisives bovine teeth were selected for the cavity preparation on the buccal surface with the gingival margin at the enamel-cement junction and occlusal margin in enamel. The materials Scotchbond Multi Purpose/3M (SBMUP) and Etch&Prime 3.0/Degussa (EP) and Z10013M composite resin were used in this study. The teeth were divided in eigth groups with 20 teeth in each froup according to the equipment and to the adhesive system used: HS + SBMUP; HS +EP; AA +SBMUP; AA + EP; US+ SBMUP; US+ EP; LA+ SBMUP; LA + EP. The restored teeth were stored at 37CC for 6 days, thermocycled (500: 5-55 C) and kept in a 2% Rodamine B solution tor 24 hours. After this they were seccioned and evaluated through stereomicroscope in order to determine the micro/eakage degree according to 0-4 score. The data were submitted to the Wilkoxon, KruskaiWal/ is and tukey statistical tests. There was significant statistical difference among the margins with the highest microleakage degrees in the cervical area; the best marginal sealing was with the US + SBMUP group. There was no significant statistical difference among the cavity preparations made with the Er:YAG laser and high-speed and high-speed and air abrasion. The highest microleakage values were found in the AA +EP group